2014
DOI: 10.1371/journal.pone.0110315
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter Peritoneal Dialysis Peritonitis: A Changing Landscape over Time

Abstract: Background Acinetobacter species are assuming an increasingly important role in modern medicine, with their persistent presence in health-care settings and antibiotic resistance. However, clinical reports addressing this issue in patients with peritoneal dialysis (PD) peritonitis are rare.MethodsAll PD peritonitis episodes caused by Acinetobacter that occurred between 1985 and 2012 at a single centre were retrospectively reviewed. Clinical features, microbiological data, and outcomes were analysed, with strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 27 publications
5
30
0
1
Order By: Relevance
“…Chao et al stated that DM and chronic glomerulonephritis are the most common causes of renal disease in the Acinetobacter peritonitis patients [9]. Similarly, our patient had comorbidity as DM, renal disease, and smoking.…”
Section: Discussionsupporting
confidence: 64%
“…Chao et al stated that DM and chronic glomerulonephritis are the most common causes of renal disease in the Acinetobacter peritonitis patients [9]. Similarly, our patient had comorbidity as DM, renal disease, and smoking.…”
Section: Discussionsupporting
confidence: 64%
“…Acinetobacter baumannii peritonitis was recently reviewed in PD patients, and the authors stated that infection with this bacterium generally results in serious peritonitis even after removal of the PD catheter (3). Acinetobacter ursingii peritonitis has been reported previously (4). However in this paper, detailed information, clinical findings, antibiotic sensitivity test and consequences of treatment were missed.…”
mentioning
confidence: 69%
“…Etiology of acute pancreatitis after renal transplantation is unclear and includes immunosuppressive drugs, alcohol consumption, hyperlipidemia, bile duct stones, hyperparathyroidism and viral infections (2,3). Sirolimus is an mTOR inhibitor commonly used for post-transplant immunosuppression, with numerous adverse effects, most commonly proteinuria, hypertrigliceridemia and leukopenia (4). We present the first reported case of a renal transplant recipient with acute pancreatitis caused by sirolimus.…”
Section: Possible Sirolimus-induced Acute Pancreatitis In a Renal Tramentioning
confidence: 98%
“…Chia et al (2014), found that Acinetobacter baumannii after 2000, was 9 (64%)was the most common species identified from the effluent, and the leading causes of infection were sterility break and GI microflora translocation (33).…”
Section: Antibiotic Sensitivitymentioning
confidence: 99%